2017
DOI: 10.1039/c7sc02574b
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic upcycling of polyacrylates through organocatalyzed post-polymerization modification

Abstract: A new method for converting commodity polymeric materials into value-added specialty materials was developed via site-selective and chemoselective transesterification of block copolymers, statistical copolymers, and homopolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 32 publications
0
88
0
2
Order By: Relevance
“…However, despite the high catalytic activity of TBD, when low molecular weight materials (<2500 Da) were targeted, the kinetics of transesterification prevailed over the ROP process, limiting the synthetic strategy toward accessing oligomeric species . In addition, TBD has the tendency to cleave BOC‐protected functionalities, leading to a fast self‐immolative degradation of the growing polymer chain when used in the presence of functional monomers …”
Section: Introductionmentioning
confidence: 99%
“…However, despite the high catalytic activity of TBD, when low molecular weight materials (<2500 Da) were targeted, the kinetics of transesterification prevailed over the ROP process, limiting the synthetic strategy toward accessing oligomeric species . In addition, TBD has the tendency to cleave BOC‐protected functionalities, leading to a fast self‐immolative degradation of the growing polymer chain when used in the presence of functional monomers …”
Section: Introductionmentioning
confidence: 99%
“…For example,previous studies have demonstrated that the simple addition of ar adical initiator during extrusion of PE/iPP blends is not av iable solution for compatibilization. [186] New Figure 13. A) Photochemicalm ethods provide opportunities for the heterogeneous functionalization of polymer surfaces that can be patterned lithographically.B )Site-selective CÀHfunctionalization can greatly increase the functionald iversity of commodity materials through simple transformations.…”
Section: Outlook and Future Directionsmentioning
confidence: 99%
“…Lastly,c ontemporary methods have been developed for the post-polymerization modification of commodity acrylate, methacrylate,a nd acrylamide monomers. [186][187][188][189] Commercial polyolefins bearing alkene functional handles have previously been modified in many post-polymerization strategies. [6,190] Although these transesterification or olefin functionalization methods do not involve C À Hfunctionalization, the concept of increasing the functional diversity of commercial polymers is similar to the work presented in this Review.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In addition, hydrolysis of the ester to the corresponding carboxylic acid can be exploited for organocatalyzed esterifications and amidations, and Ugi and Passerini multicomponent reactions . Nevertheless, the direct modification of polymers with unactivated pendant ester groups remains a challenging topic within polymer chemistry, as only recently reports have emerged of their quantitative conversion . Inspired by the guanidine‐catalyzed amidation and transesterification of polymers with pendant ester groups, we explored the use of guanidines as a reactant, rather than a catalyst, in order to synthesize the corresponding acyl guanidines.…”
Section: Introductionmentioning
confidence: 99%